2021
DOI: 10.3390/nano11010123
|View full text |Cite
|
Sign up to set email alerts
|

Optical Sensitivity of Waveguides Inscribed in Nanoporous Silicate Framework

Abstract: Laser direct writing technique in glass is a powerful tool for various waveguides’ fabrication that highly develop the element base for designing photonic devices. We apply this technique to fabricate waveguides in porous glass (PG). Nanoporous optical materials for the inscription can elevate the sensing ability of such waveguides to higher standards. The waveguides were fabricated by a single-scan approach with femtosecond laser pulses in the densification mode, which resulted in the formation of a core and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Thus, volume phase grating (VPG) was fabricated, and tracking the changes in the diffraction pattern helped to demonstrate the concept of a pHsensor. Previously, our group demonstrated the inscription of the densi cation tracks inside the plates of nanoporous silicate matrix (NPSM), where we showed the refractive index contrast up to Δn = 1.2•10 − 2 [12], and provided nanogratings with subwave periods Λ ~ 100 nm [13]. The results obtained suggest that a single layer VPG in NPSM will have the following features: (i) tunable diffraction e ciency depending on laser processing parameters; (ii) sensitivity to molecules that are captured by the nanoporous framework and (iii) the grating sensitivity to the polarization of the transmitted light due to birefringence nature of every track.…”
Section: Introductionmentioning
confidence: 86%
“…Thus, volume phase grating (VPG) was fabricated, and tracking the changes in the diffraction pattern helped to demonstrate the concept of a pHsensor. Previously, our group demonstrated the inscription of the densi cation tracks inside the plates of nanoporous silicate matrix (NPSM), where we showed the refractive index contrast up to Δn = 1.2•10 − 2 [12], and provided nanogratings with subwave periods Λ ~ 100 nm [13]. The results obtained suggest that a single layer VPG in NPSM will have the following features: (i) tunable diffraction e ciency depending on laser processing parameters; (ii) sensitivity to molecules that are captured by the nanoporous framework and (iii) the grating sensitivity to the polarization of the transmitted light due to birefringence nature of every track.…”
Section: Introductionmentioning
confidence: 86%
“…Test of waveguides was performed on the setup, whose diagram is shown in Fig. 3, c, and which we used earlier for the study of waveguides in porous glass [17]. Diagram composition: optical fiber (Thorlabs, FS-SN-3224) with the diameter of mod field 4 µm (1), NPSM plate with the waveguides recorded within the volume (2), objective (40X, 0.65 NA) (3) and CMOS camera (Gentec 3M) (4).…”
Section: Experimental Partmentioning
confidence: 99%
“…Fernandez et al [16], have shown that selection of the glass composition for writing channel waveguides has a strong effect for the waveguide propertiesoptical losses, aspect ratio and refraction index contrast. We consider an alternative base for the integration of optofluidic elementsa nanoporous silicate matrix (NPSM) [17]. These matrices are optically transparent and highly resistant against physical and chemical effects, and the nanoporous structure allows to set the properties of formed elements within a wide range.…”
Section: Introductionmentioning
confidence: 99%